Imaging Findings in Late-Onset Rectal and Vesical Bleed in Patients Who Have Undergone Radiation Therapy for Pelvic Neoplasms - Jagadeesh Pasupuleti; Yugandhar Samireddypalle; Guntaka Srujana; Ramavath Ravi Naik; Sabarinath Eada; K.S. Vedaraju (Asian Journal of Medical Radiological Research, 2020)
Radiation-induced vessel injury is described more than a century ago and remains a persistent clinical problem, despite advances in the field of radiation oncology. Treatment of pelvic neoplasms with radiotherapy may result in chronic radiation toxicity, especially Haemorrhagic radiation cystitis and chronic radiation proctitis. We discussed the computed tomography (CT) findings of three cases with a history of radiotherapy to the pelvis presenting with hematuria and hematochezia. Contrast-enhanced CT could diagnose the cause and site of bleed. All these patients were managed successfully by endoscopic coagulation.